Migration, EU integration and the Balkan Route - Kmezić, Marko 1977- (Southeast European studies, 2024)
Cover -- Half Title -- Series Page -- Title Page -- Copyright Page -- Table of Contents -- About the Contributors -- 1 Contextualizing Refugee 'crisis' and EU Integration: Interrelatedness and Mutual Reciprocity -- 2 The Eu Integration Project Through the Lens of the Balkan-route 'migrant Crisis' -- 3 EU-Turkey Relations and the Migration Issue: Transactionalism in Action -- 4 The Migration/Refugee Crisis and the (un/re)Making of Europe: Risks and Challenges for Greece -- 5 The Balkan Human Corridor and the Case of North Macedonia -- 6 The Impact of the "Refugee Crisis" on European Integration in the Field of Asylum and Migration: A Serbian Perspective -- 7 Is Bosnia and Herzegovina a New Hotspot on the Balkan Route? -- 8 Securitizing Migration in Contemporary Hungary: From Discourse to Practice -- 9 Germany After "2015": Still a Country of Immigration and Asylum? -- 10 Conclusions: The Crisis of Migrants as Opposed to the Migrant 'crisis' and the Crisis of European Solidarity -- Index.